Stabilizing Effect of PS-b-PMMA Diblock Copolymers in PS/PMMA-Based THF-in-THF Emulsions - Lee, Hyun Jung (Langmuir : the ACS journal of surfaces and colloids, 2024)
We have investigated the common solvent-based emulsion composed of polystyrene (PS) and poly(methyl methacrylate) (PMMA) solutions in tetrahydrofuran in the presence of PS-b-PMMA diblock copolymers. The stabilization effect of the diblock was determined visually and by confocal laser scanning microscopy at various phase volume fractions, concentrations, and compositions of the copolymer. The behavior of PS-b-PMMA in each homopolymer solution was studied with static and dynamic light scattering. The copolymer formed micelles above a critical homopolymer concentration. Light scattering measurements showed that small amounts of the other homopolymer added to the micelle solution entered the micelles spontaneously, suggesting that the observed emulsion stability is caused by the diblock copolymer laminar layer formation covering the surface of the dispersed droplets